Transparansi Honorarium Advokat dalam Hubungan Hukum Klien dan Pengacara - Desy Ray Evan; Putri Sari Harefa; Dinauli Adzka Nasution; Rifki Hamdani Siagian; Desta Annisa Putri; Ajeng Pratiwi; Gunawan; Siti Hasna Harahap; Nur Aisyah Siregar; Nurhotia Harahap. (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
This study examines the transparency of advocate fees (honorarium) within the client-attorney legal relationship in Indonesia. Although Article 21 of Law No. 18 of 2003 on Advocates entitles advocates to fees for their legal services, it sets no standard tariff, leaving the amount to negotiation and creating uncertainty for both parties. Using a normative legal method with statutory and conceptual approaches, supported by sociolegal insight from an expert practitioner, the study analyzes how fees are determined, the factors influencing their amount and form, and the impact of fee transformation on the client-attorney relationship. The findings show that written contracts and the Indonesian Advocates Code of Ethics are key instruments for ensuring fairness and transparency. Fees are set through agreement using schemes such as hourly, fixed, retainer, and success fees, influenced by case complexity, time, the advocate reputation, the client economic capacity, and legal risk. Transparent and proportional fee arrangements strengthen professionalism, protect client rights, and sustain trust, provided they remain consistent with professional ethics.